So your home is built on expansive soils a discussion on how expansive soils affect buildings - Wray, Warren K.; Addison, Marshall B.; Struzyk, Kenneth M. (American Society of Civil Engineers, 2019)
Prepared by the Shallow Foundations Committee of the Geo-Institute of the American Society of Civil Engineers. So Your Home is Built on Expansive Soils, Second Edition, is written for the layperson in clear, easy-to-understand terms to assist homeowners in understanding why some soils and conditions lead to problematic shrinking and swelling. Both the nature of the soil behavior and how buildings respond are addressed. This comprehensively updated report discusses the difference between cosmetic damage and structural damage resulting from soil shrinkage or heave movement and provides information on both prevention and mitigation of damage. Topics include definition and characteristics of expansive soils; building foundation types; causes of interior and exterior cracks; climate, vegetation, and landscape irrigation; homeowner maintenance; lot drainage and foundation performance; and prevention and mitigation techniques. Numerous new photographs and updated diagrams and figures illustrate key points. Also included is a section of frequently asked questions by individuals who have or are building homes on expansive soils. This book will be of interest to homeowners, as well as construction industry professionals and engineering practitioners.